Biological Activity of Quinoline Alkaloids from Raulinoa echinata and X-ray Structure of Flindersiamine - Biavatti, Maique W.; Vieira, Paulo C.; Silva, M. Fátima das G. F. da; Fernandes, João B.; Victor, Sandra R. [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Albuquerque, Sérgio; Caracelli, Ignez; Zukerman-Schpector, Julio (Sociedade Brasileira de Química, 2002)
A investigação fitoquímica dos extratos de caules e folhas da espécie endêmica Raulinoa echinata Cowan, Rutaceae, levou ao isolamento de alcalóides furoquinolínicos (esquimianina, kokusaginina, maculina e flindersiamina) e quinolônicos (1-metil-2-n-nonil-4-quinolona, 2-n-nonil-4-quinolona e 2-fenil-1-metil-4-quinolona). Os alcalóides isolados mostraram atividade antifúngica contra Leucoagaricus gongylophorus, o fungo simbionte de formigas cortadeiras (Atta spp). Quando testados in vitro contra formas tripomastigotas de Trypanosoma cruzi, os alcalóides foram inativos ou parcialmente ativos. Neste trabalho descrevem-se o isolamento dos alcalóides, a elucidação estrutural dos alcalóides quinolônicos e a estrutura obtida por difração de raio-X da flindersiamina, juntamente com os resultados dos bioensaios realizados.

Phytochemical survey of stems and leaves extracts of the South Brazilian endemic plant Raulinoa echinata Cowan, Rutaceae, led to the isolation of known furoquinoline alkaloids: the widespread skimmianine; kokusaginine, maculine, flindersiamine, and also quinolone derivatives: 1-methyl-2-n-nonyl-4-quinolone, 2-n-nonyl-4-quinolone and 1-methyl-2-phenyl-4-quinolone. These alkaloids showed antifungal activity against Leucoagaricus gongylophorus; the symbiotic fungus of leaf-cutting ants (Atta sexdens). They were inactive or displayed weak inhibitory activity when assayed in vitro against trypomastigote forms of Trypanosoma cruzi. In this paper, the isolation, structure elucidation and bioactivity results of these compounds are reported together with the X-ray structure of flindersiamine.
Keywords: Raulinoa echinata; furoquinoline and quinolone alkaloids; antifungal; Trypanosoma cruzi; X-ray structure determination